2006
DOI: 10.1016/j.jmva.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of covariance matrices in fixed and mixed effects linear models

Abstract: The estimation of the covariance matrix or the multivariate components of variance is considered in the multivariate linear regression models with effects being fixed or random. In this paper, we propose a new method to show that usual unbiased estimators are improved on by the truncated estimators. The method is based on the Stein-Haff identity, namely the integration by parts in the Wishart distribution, and it allows us to handle the general types of scale-equivariant estimators as well as the general fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Loh (1991), Mathew et al (1994), Srivastava and Kubokawa (1999), and Kubokawa and Tsai (2006) considered estimation for two independent Wishart matrices, such as B and W in the one-way classification. Minimizing the sum of entropy losses, they derived different types of joint estimators, analogous to those proposed for a single matrix, and showed that improved estimators were available that had lower risk than the unbiased or REML estimators.…”
Section: Review: Principles Of Penalized Estimationmentioning
confidence: 99%
“…Loh (1991), Mathew et al (1994), Srivastava and Kubokawa (1999), and Kubokawa and Tsai (2006) considered estimation for two independent Wishart matrices, such as B and W in the one-way classification. Minimizing the sum of entropy losses, they derived different types of joint estimators, analogous to those proposed for a single matrix, and showed that improved estimators were available that had lower risk than the unbiased or REML estimators.…”
Section: Review: Principles Of Penalized Estimationmentioning
confidence: 99%
“…. , p. When k = 2, Kubokawa and Tsai [8] showed that the estimator S i dominates the James-Stein-type minimax estimator JS i under the Kullback-Leibler loss function for each i, i = 1, 2. Let S = ( S 1 , .…”
Section: Risk Dominancementioning
confidence: 99%
“…Kubokawa and Tsai [8] further studied the estimation of multivariate components of variance in the multivariate linear regression models with effects being mixed via the Stein-Haff Wishart identity and showed that each MLE dominates the corresponding moment estimator (unrestricted MLE), but there is no report on simultaneous study. In practice, we may be interested in the estimation problem of unknown covariance matrices for the completely balanced multivariate multi-way random effects models without interactions, which allow more than two unknown covariance matrices to be involved.…”
Section: An Applicationmentioning
confidence: 99%
See 2 more Smart Citations